Exploring Collaborative and Community Based Planning in Tourism Case Study Sitia-Cavo Sidero Project - Katsouli, Penelope (2007)
The present paper has explored the policy planning and development in emerging tourism settings in Sitia. Comprehensively, this study, in the name of sustainable development, focused on the extent of collaborative and community-based planning. For that reason exploratory research has been used; the context and the structure of this paper aimed to uncover the socially constructed reality of Sitia's stakeholders, within the dynamic environment, and respond to and questions. Therein significant was the contribution of eight different interviewees, closely related with the field, as well as the obtained secondary data that provided valuable indeed background information (Bryman & Bell, 2003).Briefly, a limited scope of collaboration has been implied within the Sitia's district, as the range of participants is not representative of all the affected bodies by tourism development, instead it would be better to talk of a private and public sector cooperation (Timothy, 1998). Thereby, the intensity of collaboration is also limited; during the 15 years of negotiation about the Cavo Sidero investment limited working groups, conferences and surveys took place that indicate low direct interaction among stakeholders and minimal information dissemination (Bramwell and Sharman, 1999). So, whilst accepting the spatial proximity of local authorities to the domain and to the community the need to empower them came at the forefront. Further, from a long term perspective local authorities enriched with special skilled human resources and in concert with the private sector should invest on building community capacity through education and raise of self awareness, in order locals to be capable of coping with complex and demanding issues and thenÃ¢ÂÂÃÂÃÂundertaking projects with independence and skills (Jamal and Lagiewski, 2006, p. 2).